Karakterisasi Morfologi Anggrek Phalaenopsis Hibrida - Pangestu, Fajar; Arifin Aziz, Sandra; Sukma, Dewi (Jurnal Hortikultura Indonesia, 2015)
ABSTRACTOrchid is one of ornamental plants that  has  high aesthetic value and Phalaenopsis hybrid is one of orchid type  famous in Indonesia. Characterization of Phalaenopsis hybrid should be made to determine  similarity  or  diversity between  hybrids  and  as  a  basic  information  on  plant  breeding activities. The purpose of this study was to study the morphological character and relationship of five  accessions  of Phalaenopsis  hybrid  i.e,  four white accessions  flowering hybrid, one  accession yellow flowering hybrids and Phalaenopsis  amabilis  ‘Cidaun’  ecotype. Based on the morphology of leaves and  flowers,  two  of  the  four  accessions  white  flowering  hybrid  have similarity  coefficient 1.00. Every Phalaenopsis hybrid clustered together on the similarity coefficient 0.729, but one of three replications yellow flowering hybrids have similarity coefficient 0.435 with main differences in leaf shape and flowering types.  Phalaenopsis  amabilis’  Cidaun’  ecotype  have similarity coefficient 0.528 with main differences with Phalaenopsis hybrid in flowers shape and flowering types.Keywords: Coefficient similarity, flowers, leaves, morphological character, Phalaenopsis hybrid ABSTRAKAnggrek  merupakan  tanaman  hias  yang  memiliki  nilai  estetika  tinggi  dan Phalaenopsishibrida  merupakan  salah  satu  jenis  anggrek  yang  terkenal  di Indonesia.  Keragaman  Phalaenopsishibrida  yang  cukup  tinggi,  sehingga perlu  dilakukan  karakterisasi  untuk  mengetahui  kemiripan ataupun keragaman  antar  Phalaenopsis  hibrida  maupun  dengan  Phalaenopsis spesies asli  sebagai informasi  dasar  dalam  kegiatan  pemuliaan  tanaman.  Tujuan dari  penelitian  ini  adalah  untuk mempelajari  karakter  morfologi  dan kekerabatan  antara  lima  aksesi  Phalaenopsis  hibrida  yaitu empat aksesi hibrida berbunga putih, satu aksesi hibrida berbunga kuning dan Phalaenopsis amabilisekotipe ‘Cidaun’. Berdasarkan morfologi daun dan bunga, dua dari empat aksesi hibrida berbunga putih  memiliki  koefisien  kemiripan  1.00. Semua  Phalaenopsis  hibrida  berkelompok  menjadi  satu pada  koefisien kemiripan  0.729,  sementara  satu  ulangan  dari  hibrida  berbunga  kuning memiliki koefisien  kemiripan  0.435  dengan  perbedaan  utama  pada  bentuk daun  dan  tipe  pembungaan. Phalaenopsis  amabilis  ekotipe  ‘Cidaun’ memiliki koefisien kemiripan 0.528 dengan  Phalaenopsishibrida, perbedaan utama pada bentuk bunga dan tipe pembungaan.Kata kunci: Koefisien kemiripan, Bunga, daun, karakter morfologi, Phalaenopsis hibrida